On the freedom side : how five decades of youth activists have remixed American history - Hogan, Wesley C. (The University of North Carolina Press, 2019)
"As Wesley C. Hogan sees it, the future of democracy belongs to young people. While today's generation of leaders confronts a daunting array of existential challenges, increasingly it is young people in the United States and around the world who are finding new ways of belonging, collaboration, and survival. That reality forms the backbone of this book, as Hogan documents and assesses young people's interventions in the American fight for democracy and its ideals. Beginning with reflections on the inspiring example of Ella Baker and the Student Nonviolent Coordinating Committee in the 1960s, Hogan profiles youth-led organizations and their recent work. Examples include Southerners on New Ground (SONG) in the NAFTA era; Oakland's Ella Baker Center and its fight against the school-to-prison pipeline; the Dreamers who are fighting for immigration reform; the Movement for Black Lives that is demanding a reinvestment in youth of color and an end to police violence against people of color; and the International Indigenous Youth Council, water protectors at Standing Rock who fought to stop the Dakota Access Pipeline and protect sovereign control of Indigenous lands. As Hogan reveals, the legacy of Ella Baker and the civil rights movement has often been carried forward by young people at the margins of power and wealth in U.S. society. This book foregrounds their voices and gathers their inventions--not in a comprehensive survey, but as an activist mix tape--with lively, fresh perspectives on the promise of twenty-first-century U.S. democracy"--